A novel fluorescent amphiphilic glycopolymer based on a facile combination of isocyanate and glucosamine1. Issue 8 (28th February 2015) - Zhang, Xiqi; Zhang, Xiaoyong; Wang, Ke; Liu, Hongliang; Gu, Zhen; Yang, Yang; Wei, Yen
<x xml:space="preserve">Abstract</x> A novel fluorescent amphiphilic glycopolymer was synthesized through radical polymerization and subsequent glycosylation with glucosamine, and self-assembled into nanoparticles for cell imaging.